A more detailed view of reactive oxygen species metabolism in the sugarcane and Sporisorium scitamineum interaction - Peters, Leila Priscila (2016)
Sugarcane (Saccharum spp) is an important commercial crop cultivated widely in tropical and subtropical countries. Primarily sugarcane is used to produce sugar and recently it is proven to be a valuable resource for bioethanol, biodiesel, bioplastic and bioelectricity. Smut is one of the most serious sugarcane disease and occurs in sugarcane fields all over the world. The disease is caused by the biotrophic fungus Sporisorium scitamineum. The fungus induces metabolic changes in the plant leading to the production of a whip-like structure where fungal sporogenesis take place. The objective of this study was to analyse the reactive oxygen species (ROS) production, antioxidant enzymes activity and expression of genes associated with the ROS metabolism in smut susceptible (IAC66-6) and resistant sugarcane genotypes (SP80-3280). In addition, this work assessed the relationship between antioxidant enzymes and sensitivity of S. scitamineum to exogenous hydrogen peroxide (H2O2). This thesis is presented in the format of two chapters (chapters 2 and 3). In the second chapter, the results revealed that there were variations in the antioxidant system as well as in the ROS production in resistant sugarcane genotype, whereas few changes occurred in the susceptible genotype inoculated with S. scitamineum. Microscopic analysis revealed that S. scitamineum teliospore germination and appressorium formation were delayed during early infection in the smut resistant genotype, which coincided with H2O2 accumulation. In chapter 3, the results demonstrated that S. scitamineum is highly resistant to exogenous H2O2. At 2 mM exogenous H2O2 concentration the fungus presented an effective antioxidant system in response to the secondary products of oxidative stress. Furthermore, S. scitamineum when exposed for a long time at 2 mM exogenous H2O2 concentration it can acquire an adaptive response to H2O2. The results obtained in this study contributed to increase the understanding of this very complex interaction between sugarcane and S. scitamineum and it will be helpful toward understanding which aspects are involved in the resistance to S. scitamineum. These informations are important to create strategies for improving smut resistance in sugarcane.